Making money out of publicly available information - Morrison, A; Vulkan, N (University of Oxford, 2003)
It is received financial wisdom that when there is free entry by speculators, it is impossible to generate net profits on publicly available information. In this paper we study a version of the standard Kyle (85) model with endogenous information acquisition and we find that equilibria exist with free entry in which speculators make positive profits. Moreover, these equilibria are robust.